Ethnicity and Second Generation Immigrants in Britain - Christian Dustmann; Tommaso Frattini; Nikolaos Theodoropoulos (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
This paper reviews the labour market performance and educational attainment of ethnic minorities and second generation immigrants in the UK over the last three decades. We first describe the size and composition of the minority population and its regional distribution over time, and investigate their labour market performance relative to the white native population. We then present an intergenerational comparison of education, employment, and wages of different ethnic minority groups born in Britain to their parents' generation, and to equivalent groups of white native born individuals. We conclude with a summary of recent research on the school performance of children from ethnic minorities relative to their white peers.
Keywords: J15; J61; J62; 330; Ethnic minorities; Second generation immigrants; Intergenerational comparison